Between Afro-Brazilian fashion and aesthetic-politics: a digital information analysis carried out in the daily struggles of black activist from Caruaru - Suellen Arcoverde Moreira, Vanessa; Zimmerle da Nóbrega Costa, Flávia; Alice Vasconcelos Rocha, Maria (InfoDesign, 2024)
Being a black woman in Brazil is a challenging role to assume, as they are burdened by the legacies of racism, sexism and economic vulnerability. Incessant forms of struggle shape their daily lives and one of the main strategies of their activist practices is political aesthetics, considered essential for their social representation. Given this context, this research aimed to reveal: How does the political aesthetics present in Afro-Brazilian fashion act in the struggles of black activists from Caruaru on digital networks? Our archive was composed of 1,586 documents collected from digital social media, published by black activists. Inspired by Foucaultian Discourse Analysis, we unveiled the statements and their synchronous and incidental relationships. Such discursive relationships showed how the informational elements of this aesthetic materialize an identity based on ancestry, capable of evoking mutual support and the effectiveness of actions in this context.